Office management : principles and practice - McBride, Margaret. (Thomas Nelson Australia, 1993)
Office administration in the information age. Principles of office administration. Administrative office systems. Decision-making, problem-solving and productivity. Improving office productivity. Communication in the office. Supervising the office staff. Recruiting and orienting the office staff. Training, appraising and promoting office personnel...